For the sake of heaven and earth the new encounter between Judaism and Christianity - Greenberg, Irving, 1933- (Philadelphia : Jewish Publication Society, 2004)
A pioneer in the area of pluralism and interfaith relations, Rabbi Irving Greenberg has spent a lifetime working to overcome the history of hostility between Judaism and Christianity. This book is studded with provocative ideas, which challenge believers on both sides to grow in good faith. In sum, this book is a call for Christians and Jews to work closely together in their evolving partnership with God. Rabbi Greenberg takes us along on a personal journey, initially stimulated by his research on Holocaust testimony, that led to his rethinking of Christianity, and that ultimately gave rise to his belief that Christianity, Judaism, and indeed every religion that works to repair the world and advance the triumph of life, are valid expressions of the universal bond (brit) between God and humankind. In the second part of his book, Greenberg brings together, for the first time, seven of his most important essays on the new encounters between Judaism and Christianity in our generation. It concludes with a study guide and powerful responsive essays by leading Catholic, Protestant, and Jewish commentators, James Carroll, Michael Novak, Mary C. Boys, Krister Stendhal, and David Novak. - Back cover.
On the road to a new encounter between Judaism and Christianity: a personal journey -- Covenantal partners in a postmodern world -- The new encounter of Judaism and Christianity -- New revelations and new patterns -- Toward an organic model of the relationship -- The respective roles of the two faiths in the strategy of redemption -- Covenantal pluralism -- Pluralism and partnership -- Covenants of redemption.
Includes bibliographical references and index.
Print version record.
Keywords: Judaism -- Relations -- Christianity -- 1945-; Christianity and other religions -- Judaism -- 1945-; Covenants -- Religious aspects -- Judaism; Christianity; Covenants -- Religious aspects -- Judaism; Interfaith relations; Judaism; Christentum; Judentum; RELIGION / Judaism / General; Since 1945; Electronic books